Inter-method and anatomical correlates of episodic memory tests in the Alzheimer’s Disease spectrum - Sudo, Felipe Kenji; de Souza, Andrea Silveira; Drummond, Claudia; Assuncao, Naima; Teldeschi, Alina; Oliveira, Natalia; Rodrigues, Fernanda; Santiago-Bravo, Gustavo; Calil, Victor; Lima, Gabriel; Erthal, Pilar; Bernardes, Gabriel; et al. (PloS one, 2019)
Episodic memory impairments have been described as initial clinical findings in the Alzheimer's Disease (AD) spectrum, which could be associated with the presence of early hippocampal dysfunction. However, correlates between performances in neuropsychological tests and hippocampal volumes in AD were inconclusive in the literature. Divergent methods to assess episodic memory have been depicted as a major source of heterogeneity across studies. We examined correlates among performances in three different delayed-recall tasks (Rey-Auditory Verbal-Learning Test-RAVLT, Logical Memory and Visual Reproduction subtests from the Wechsler Memory Scale) and fully-automated volumetric measurements of the hippocampus (estimated using Neuroquant®) of 83 older subjects (47 controls, 27 Mild Cognitive Impairment individuals and 9 participants with Dementia due to AD). Inter-method correlations of episodic memory performances were at most moderate. Scores in the RAVLT predicted up to 48% of variance in HOC (Hippocampal Occupancy Score) among subjects in the AD spectrum. Tests using different stimuli (verbal or visual) and presenting distinct designs (word list, story or figure learning) may assess divergent aspects in episodic memory, with heterogeneous anatomical correlates. Different episodic memory tests might not assess the same construct and should not be used interchangeably. Scores in RAVLT may correlate with the presence of neurodegeneration in AD.